Pharmacokinetics and safety of highly variable nitroglycerin lingual spray (NLS) versus US-licensed nitroglycerin lingual spray reference product (Nitrolingual®): a randomized, four-cycle, four-sequence, partially replicated crossover Phase I bioequivalence clinical trial - Fang, Yingying; Qi, Lu; Wang, Yu; Han, Chunyu; Zhang, Qian; Liu, Xiaoyun; Liu, Ju; Cheng, Xiaoqiang; Li, Yinjuan; Li, Yan; Sun, Mingli; Liu, Long; et al. (Frontiers in Pharmacology, 2025)
PurposeIn this Phase I study, we aimed to evaluate the pharmacokinetic bioequivalence and the safety of a nitroglycerin lingual spray (NLS) compared with US-approved Nitrolingual in healthy subjects.MethodsSubjects (N = 56) were randomized 1:1 to receive one 96-mg NLS, US-approved Nitrolingual; safety was assessed for 11 days. Bioequivalence was evaluated using the average bioequivalence method to test whether the 90% confidence intervals (CIs) of the geometric means (NLS vs. US-approved Nitrolingual) for the primary endpoints were within prespecified acceptable ranges (80%–125%).ResultsAfter the single administration of NLS (test preparation vs. reference preparation) under fasting conditions, the geometric mean ratios (GMRs) of Cmax, AUC0−t, and AUC0−∞ were 108.08%, 108.20%, and 110.85%, respectively. For the primary metabolites of NLS (1, 2-GDN), the GMRs of Cmax, AUC0−t, AUC0−∞ were 107.68%, 102.28%, and 102.23%, respectively. Similarly, for another metabolite of NLS (1, 3-GDN), the GMRs of Cmax, AUC0−t, and AUC0−∞ were 106.56%, 102.05%, and 104.67%, respectively. All 90% CIs for the test/reference AUC ratio and Cmax ratio were within the acceptable range (80%–125%) for BE, which met the requirements of bioequivalence. No serious adverse events (AEs) occurred, and all AEs were mild and transient.ConclusionThe bioequivalence of NLS to US-approved Nitrolingual was demonstrated; the safety results of the two study drugs were also similar. These studies provided robust evidence of the pharmacokinetics similarity between NLS and US-approved originator Nitrolingual.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/index.html, identifier CTR20230675.